Physical Activity Knowledge, Attitude, and Behaviours Among Adolescents in the Kingdom of Saudi Arabia Prior to and during COVID-19 Restrictions - Naif Almutairi; Sharyn Burns; Linda Portsmouth (Hindawi Limited, 2022)
Background. The prevalence of childhood and adolescent obesity has increased dramatically and poses a major public health threat globally. In the Kingdom of Saudi Arabia (KSA), the main cause of adolescent obesity is an increase in physical inactivity and unhealthy eating habits due to lifestyle changes. This study reports on factors associated with physical activity (PA) prior to and during the coronavirus disease of 2019 (COVID-19) among middle school students in Jeddah, KSA. Method. A cross-sectional online survey was conducted in Jeddah, KSA among 1500 middle school students aged 11 to 15 years. Sociodemographic characteristics; PA knowledge, attitude, and behaviours; and information about the impact of COVID-19 on PA were collected. Knowledge, attitude, and behaviours of PA before and during COVID-19 restrictions and between gender were compared. Regression analyses were conducted to assess the determinants of PA. Results. Female students were significantly more likely to report better knowledge of PA compared to males (p<0.001). However, males were significantly more likely to participate in PA compared to females (p<0.001). Approximately 60% of students reported their PA decreased during COVID-19 isolations. Most students did not participate in the recommended levels of daily PA during COVID-19 lockdowns and school closures. After adjusting for demographics, knowledge, and attitude, students who did not usually participate in school sports (p=0.017) and as members of clubs (p=0.002) were less likely to be active during COVID-19 lockdown. Conclusions. Efforts to enhance PA should be implemented through coordinated school and community-based programs to achieve the recommended PA among adolescents at home and in schools. Policy to ensure students receive PA opportunities at school is recommended.